Antecedentes de las intenciones de abandono en cooperativas colombianas (2014)
ABSTRACT: This paper presents a study on the intentions to quit of employees working in Colombian cooperatives. These enterprises were created to include woman affected by political violence into the labor market. According to some scholars, cooperative enterprises driven by a fundamental social mission face retention and recruitment problems. 332 workers participated in the survey. Structural Equation Modeling was used for data analyses. The findings suggest that within this type of enterprise, leader-member exchange has a negative indirect effect on turnover intentions. Consistent with previous research, this relationship is mediated by perceived organizational support. Moreover, the relationship between leader-member exchange and turnover intentions is also mediated by job-embeddedness. The limitations of the study as well as practical and theoretical implications are presented at the end of the paper.